"It's really geniuses that live in the hood": Black urban youth curricular un/makings and centering Blackness in slavery's afterlife. Issue 1 (5th December 2020) - Coles, Justin A.
Abstract: Curriculum within the US was birthed in a context of antiblackness and continues to operate as anti-Black through imagining Black youth as less than and uneducable. However, despite the ways educational space has historically worked to image Black children and communities through deficit lenses, the creation of non-traditional Black curricular spaces has long served as a strategy of resistance. In this paper, I examine the ways Black urban youth leveraged a co-created non-traditional curricular space, grounded in centering Blackness to make sense of their educational experiences. I draw from an academic yearlong (2016–2017) critical ethnography, centered in Black Critical Theory (BlackCrit), to examine what is revealed about Black living and learning and curriculum, through centering Blackness in a non-traditional curricular space. Theoretically framed through BlackCrit and Sharpe's (2016 ) concept of wake work, I analyze critical literacy artifacts and interview data to examine how centering antiblackness, a strength-based positioning, facilitated Black curricular un/makings that worked to: 1) center Black empowerment and 2) affirm Black knowledge. I use the term curricular un/makings to represent the ways the Black youth leveraged their life-worlds to disrupt or abandon nation-state curriculum (unmake anti-Black curricular space) to compose new ideations of curriculum and curricular space (make curriculum anew by centering Blackness). Black curricular un/makings represent the intentional process of deconstructing anti-Black curriculum through an unapologetic centering of a Black ethos.